2017
DOI: 10.1186/s13045-017-0508-x
|View full text |Cite
|
Sign up to set email alerts
|

The distinct biological implications of Asxl1 mutation and its roles in leukemogenesis revealed by a knock-in mouse model

Abstract: Background Additional sex combs-like 1 (ASXL1) is frequently mutated in myeloid malignancies. Recent studies showed that hematopoietic-specific deletion of Asxl1 or overexpression of mutant ASXL1 resulted in myelodysplasia-like disease in mice. However, actual effects of a “physiological” dose of mutant ASXL1 remain unexplored.MethodsWe established a knock-in mouse model bearing the most frequent Asxl1 mutation and studied its pathophysiological effects on mouse hematopoietic system.ResultsHeterozygotes (Asxl1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 48 publications
3
30
0
Order By: Relevance
“…Mutations in ASXL1 are associated with poor prognosis across the spectrum of malignant myeloid diseases (Gelsi-Boyer et al, 2012;Micol and Abdel-Wahab, 2016), and nearly all ASXL1 mutations lead to the production of C-terminally truncated mutant ASXL1 proteins. To study the oncogenic roles of C-terminally truncated ASXL1, previous studies have employed either transgenic expression (Inoue et al, 2013;Yang et al, 2018) or knock-in mouse models (Hsu et al, 2017;Nagase et al 2018). It has to be noted that transgenic expression is an overexpression system, and knock-in mouse models investigate the effect of Asxl1 mutation in the absence of other collaborative leukemic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in ASXL1 are associated with poor prognosis across the spectrum of malignant myeloid diseases (Gelsi-Boyer et al, 2012;Micol and Abdel-Wahab, 2016), and nearly all ASXL1 mutations lead to the production of C-terminally truncated mutant ASXL1 proteins. To study the oncogenic roles of C-terminally truncated ASXL1, previous studies have employed either transgenic expression (Inoue et al, 2013;Yang et al, 2018) or knock-in mouse models (Hsu et al, 2017;Nagase et al 2018). It has to be noted that transgenic expression is an overexpression system, and knock-in mouse models investigate the effect of Asxl1 mutation in the absence of other collaborative leukemic mutations.…”
Section: Discussionmentioning
confidence: 99%
“…It was already detected as a component of the PR-DUB complex, related to the deubiquitination of histone H2A [89]. Mice models carrying ASXL1 mutation showed myeloid dysplasia and shorter survival, mainly due to PRC2 inactivation [90]. Mutations in the ASXL1 gene have been described in many subtypes of myeloid malignancies and are associated with adverse prognosis, shorter OS and higher risk of progression [88,91].…”
Section: Asxl1 Mutationsmentioning
confidence: 99%
“…ASXL1 forms a complex with the deubiquitination enzyme BAP1 and removes monoubiquitin from H2AK119Ub, to derepress genes targeted by PRC1 [ 91 ]. Recent studies using mice expressing an ASXL1 mutant demonstrated that an ASXL1 mutation alone is not sufficient for inducing the development of hematologic malignancies [ 92 94 ]. However, an ASXL1 mutation increased the susceptibility to leukemogenesis in concert with a RUNX1 mutant or in viral insertional mutagenesis, indicating that mice expressing an ASXL1 mutant represent a premalignant condition like ARCH/CHIP [ 93 ].…”
Section: Main Textmentioning
confidence: 99%